URGENSI PENDIDIKAN BAHASA INGGRIS DAN PENDIDIKAN KRISTEN BAGI ANAK-ANAK DI DESA BATU TUKAN - Dato, Rida Nadia Pavlin; Sabolak, Floranita (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
English education must be taught in every school at every level because English is currently a unifying language between countries or an international language. Not much different from English education, Christian religious education is also a mandatory lesson that must be held at every level of education because it is the basis and principles of the Christian faith, focusing on biblical principles, character, etc. Including English language education and Christian religious education as mandatory subjects at the primary school level has a terrible impact on children, resulting in village children falling behind cognitively and being unable to compete with students who receive education in cities. Therefore, the author took the initiative to dedicate himself to improving village children by holding English lessons that were open to the public and holding a Sunday School for Christian children. The approach method that the author used was quite effective, as evidenced by the increasing enthusiasm of the children in participating in the existing program. Even though there are many pros and cons from various parties, the author is grateful that the program that the author has implemented has produced satisfactory results, as proven by the children's starting to understand the basics of learning that the author shares.